COVID-19 and trained immunity: the inflammatory burden of long covid - Gu, Jienan; Liu, Qianhui; Zhang, Jiale; Xu, Shijie (Frontiers in Immunology, 2023)
Severe COVID-19 elicits excessive inflammation mediated by innate immune cells like monocytes. Recent evidence reveals extensive epigenetic changes in monocytes during recovery from severe COVID-19, including increased chromatin accessibility at genes related to cytokine production and leukocyte activation. These changes likely originate from the reprogramming of upstream hematopoietic stem and progenitor cells (HSPCs) and represent "trained immunity". HSPC-to-monocyte transmission of epigenetic memory may explain the persistence of these monocyte alterations despite their short lifespan. IL-6 appears pivotal for imprinting durable epigenetic modifications in monocytes during acute infection, with IL-1β potentially playing a contributory role. The poised inflammatory phenotype of monocytes post-COVID-19 may drive chronic inflammation and tissue damage, contributing to post-acute sequelae of COVID-19 symptoms. COVID-19 could also exacerbate inflammation-related diseases, such multisystem inflammatory syndromes, by altering innate immune tendencies via hematopoietic epigenetic reprogramming. Further clinical investigations quantifying inflammatory mediators and mapping epigenetic changes in HSPCs/monocytes of recovering patients are warranted. Research should also examine whether COVID-19 elicits transgenerational inheritance of epigenetic alterations. Elucidating mechanisms underlying COVID-19-induced monocyte reprogramming and developing interventions targeting key inflammatory regulators like IL-6 may mitigate the sustained inflammatory burden imposed by the aberrant trained immunity post-COVID-19.